Characterization of Estrous Cycle in Rats Through Morphological and Cytological Changes in Tubular Genitalia - Kumar, Shubham; Kumar Shukla, Manish; Tripathi, Ashutosh; Kumar Verma, Atul; Kapoor, Neelesh; Kumar, Pradeep; Kumar, Aditya; Gautam, Jaipal (The Indian Journal of Animal Reproduction, 2026)
In the present study the phases of estrous cycle of the albino Wistar rats were characterized so as to carry out reproduc tive procedure like superovulation. The phases of estrous cycle of rats in the present study were characterized by two methods e.g. visual examination by recording morphological changes in vulva and vagina and vaginal cytology meth ods. The various morphological changes noticed in vulva and vagina during the proestrus phase were: initiation of the vaginal opening, moist and reddish pink vaginal tissues and appearance of longitudinal folds on the vulvar lip. During estrus phase vaginal opening was nearly similar to proestrus phase but the vaginal tissues appeared lighter pink and less moist. The longitudinal folds during estrus appeared more pronounced than proestrus. The swelling on the dorsal lip got reduced while vaginal tissues appeared pale and dry during metestrus. There was no vaginal opening noticed during diestrus while the vaginal tissues appeared moist. The cytological changes noticed were as follows: the predominance of small nucleated cells (80%) was noticed during the proestrus phase while the estrus phase was characterized by the predominance of anucleated cornified epithelial cells (80%). There were large number of PMN cells (65%) with few anucleated cornified cells (20%) during metetrus phase. The diestrus phase was characterized by predominance of Polymorphonuclear (PMN) cells (80%). Thus, phasing of estrous cycle of rat can be efficiently performed with visual examination supported by vaginal cytology for its confirmation.
Keywords: Cornified epithelial cells; Estrous cycle; Polymorphonuclear cells; Rats; Small nucleated cells; Visual examination